2012
DOI: 10.1007/s12663-012-0452-9
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, Incidence and Patterns of Mid-Face Fractures and Associated Ocular Injuries

Abstract: A prospective study on mid-face fractures was carried out in the Department of Oral and Maxillofacial Surgery at College of Dentistry, Indore, from August 2007 to September 2009 to analyze etiology, incidence and patterns of midface fractures and associated ocular injuries. Two hundred patients were included in this study, amongst those who reported to the Department of OMFS, College of Dentistry, Indore. After confirmed diagnosis of mid face fracture all the patients were stratified according to age, sex, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
60
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 24 publications
20
60
8
1
Order By: Relevance
“…Hyphema or bleeding in the anterior chamber is mostly caused due to tearing of blood vessels at the root of the iris. 1,11,15 In this study, hyphema/anterior chamber injury was present in 12.3%, which is slightly higher than in other studies.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…Hyphema or bleeding in the anterior chamber is mostly caused due to tearing of blood vessels at the root of the iris. 1,11,15 In this study, hyphema/anterior chamber injury was present in 12.3%, which is slightly higher than in other studies.…”
Section: Discussioncontrasting
confidence: 69%
“…This was slightly lower than that reported by Septa et al (3.16:1), Cheema, and others. 1,3 This shows that females are more involved in social activities and frequently using MTW for the mode of transportation in our population. Previous studies have reported that the zygomatic complex fracture was the most common type in all facial middle third injuries.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…19,20,21 The etiology of maxillofacial & concomitant injuries in our study results clearly indicated RTA was the widespread causative factor followed by assaults, which were similar with the studies conducted in different parts of world. 15,19,22,23 Maxillofacial injuries are barely fatal; however these injuries certainly cause physical/ psychological stress to the patient. 16 Maxillofacial injuries might comprise upper third, middle third, and/or lower third of the face, inclusive or exclusive of soft tissue injury & most of the times dentition possibly will also have injuries i.e.…”
Section: Resultsmentioning
confidence: 99%